1993
DOI: 10.1177/030089169307900513
|View full text |Cite
|
Sign up to set email alerts
|

Plasma D-Dimer Measurement as a Marker of Gynecologic Tumors: Comparison with CA 125

Abstract: Our results suggest that D-dimer can serve as a sensitive indicator to monitor the extent and course of the disease in ovarian cancer patients. The patient follow-up is ongoing to establish the predictive value of D-dimer measurement with respect to prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…A total of 7 studies [22,24–26,3234] involving 366 ovarian cancer patients and 233 benign controls investigated the association between D-dimer and ovarian cancer. Our results showed that patients with ovarian cancer (stages I–IV) showed a higher D-dimer level compared with benign controls (SMD  =  0.774, 95% CI: 0.597–0.951), with low degree of heterogeneity ( P   =  .390, I 2   =  4.9%, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 7 studies [22,24–26,3234] involving 366 ovarian cancer patients and 233 benign controls investigated the association between D-dimer and ovarian cancer. Our results showed that patients with ovarian cancer (stages I–IV) showed a higher D-dimer level compared with benign controls (SMD  =  0.774, 95% CI: 0.597–0.951), with low degree of heterogeneity ( P   =  .390, I 2   =  4.9%, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…32 It is a sensitive marker of the fibrinolytic enhancement. 32 As in many other human malignancies, [33][34][35][36][37][38] including lung carcinoma, DD might have prognostic significance. 12,15,39 In 1993, Seitz et al 12 reported that TAT and DD were significantly increased in patients with metastatic disease and that elevated TAT values at diagnosis might be prognostically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, d ‐dimer is considered a marker for hypercoagulopathy. Indeed, elevated plasma d ‐dimer concentrations correlate with tumor progression in various malignancies, including esophageal cancer, lung cancer, colorectal cancer, ovarian cancer, cervical cancer of the uterus, and prostate cancer 17–22 . Recent data have suggested that antithrombotic therapy, such as platelet inhibitors, heparin, and low molecular weight heparin, may affect tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, elevated plasma -dimer concentrations correlate with tumor progression in various malignancies, including esophageal cancer, lung cancer, colorectal cancer, ovarian cancer, cervical cancer of the uterus, and prostate cancer. [17][18][19][20][21][22] Recent data have suggested that antithrombotic therapy, such as platelet inhibitors, heparin, and low molecular weight heparin, may affect tumor progression. In fact, several studies have suggested that the combination of chemotherapy and antithrombotic agents could prolong survival of cancer patients.…”
Section: Introductionmentioning
confidence: 99%